Development of Problem, YouTube and ChatGPT Learning Model to Improve Students’ Proving Ability in Real Analysis - Mairing, Jackson Pasini; Rizaldi, Muhammad; Pandiangan, Pantur; Lada, Elyasib Yunas; Monita, Dita Monita (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
The lack of experience and ability to construct logical, deductive, rigorous, and definite mathematical proofs is the main difficulty for students in addressing problems to prove of Real Analysis. The difficulties faced by students in solving the problems could be overcome by implementing a suitable learning model. The developmental process of problem-solving-oriented learning models with the assistance of tools in solving the problems is an appropriate solution to overcome the difficulties. Students will always be faced with the problems to enhance their experience, and by utilizing resources such as YouTube videos and ChatGPT, they will increase their knowledge to produce the proofs. The research aimed to develop a PYChat (Problem, YouTube, and ChatGPT) model in fulfilling the criteria of valid, effective, and practical while enhancing students' ability to solve problems. The model was produced through developmental research. The research works in several stages, including planning the initial product and research instruments, an exploratory study, developing the initial product, validating the initial product, and field testing. The subjects were mathematics education students from a state university in Central Kalimantan who were taking Real Analysis course in the academic year 2023/2024. The research instruments included the expert validation sheet, the observation sheet, the mid-test, the final test, and the initial product of the PYChat model consisted of the learning plan, the worksheets, and the module contained ChatGPT tasks and YouTube videos links. The research results indicated that the model met validity criteria based on the average scores of the validity model by two experts was 84. The score means the model was concluded in the very valid category. The model was effective according to research findings, showing that the students in the PYChat class scored higher than those in the PBL (Problem-Based Learning) class. The PBL model has come to use in the course of the past three years. In addition, the PYChat model was proven to be practical since its syntaxes could be applied effectively by the lecturer, and all groups submitted the problem solutions in each meeting. Therefore, using ChatGPT in mathematical learning has potential for the future. Kurangnya pengalaman dan kemampuan untuk menyusun bukti matematika yang logis, deduktif, teliti, dan jelas merupakan kesulitan utama bagi mahasiswa dalam menangani masalah pembuktian Analisis Real. Kesulitan yang dihadapi oleh mahasiswa saat menyelesaikan masalah pembuktian Analisis Real dapat diatasi dengan menerapkan model pembelajaran yang sesuai. Pengembangan model pembelajaran yang berorientasi dengan penyelesaian masalah dengan alat bantu dalam penyelesaian masalah tersebut merupakan solusi yang sesuai untuk mengatasi kesulitan tersebut. Mahasiswa akan selalu berhadapan dengan masalah pembuktian untuk menambah pengalaman mereka dan dengan memanfaatkan video YouTube dan ChatGPT akan menambah pengetahuan mereka untuk membuat pembuktian tersebut. Penelitian ini bertujuan untuk mengembangkan model pembelajaran PYChat (Problem, YouTube, dan ChatGPT) yang valid, efektif, dan praktis untuk meningkatkan kemampuan mahasiswa dalam menyelesaikan masalah pembuktian Analisis Real. Model tersebut dihasilkan melalui penelitian pengembangan. Tahap-tahap penelitiannya adalah perencanaan produk awal dan instrument penelitian, studi eksplorasi, pengembangan produk awal, validasi produk awal dan uji lapangan. Subyek penelitiannya adalah mahasiswa Pendidikan matematika dari salah universitas negeri di Kalimantan Tengah yang mengambil mata kuliah Analisis Real di tahun akademik 2023/2024. Instrumen penelitiannya adalah lembar validasi ahli, lembar pengamatan, ujian tengah semester, ujian akhir semester, produk awal dari model PYChat yang terdiri dari rencana pembelajaran semester, lembar kerja, dan modul yang memuat tugas ChatGPT dan link video YouTube. Hasil penelitian menunjukkan model PYChat memenuhi kevalidan berdasarkan rata-rata skor validitas model oleh dua ahli adalah 84, yang berarti bahwa model PYChat termasuk dalam kategori sangat valid. Model PYChat efektif berdasarkan temuan penelitian yang menunjukkan bahwa mahasiswa di kelas PYChat memiliki skor lebih dari kelas PBL (Problem Based Learning). Model PBL telah dilaksanakan dalam tiga tahun terakhir dalam mata kuliah tersebut. Selain itu, model PYChat terbukti praktis karena dalam implementasinya seluruh sintaks PYChat dapat diterapkan dengan baik oleh dosen, dan semua kelompok mengumpulkan penyelesaian dari masalah di setiap pertemuan. Dengan demikian, penggunaan ChatGPT dalam pembelajaran memiliki potensi di masa mendatang.